Isolation and identification of compounds from Bauhinia championii (Benth.) Benth - Wei Xu; Kedan Chu; Huang Li; Yuqin Zhang; Mingqing Huang; Mei Sha; Lidian Chen (International Journal of Phytomedicine, 2013)
Phytochemical investigation of Bauhinia championii (Benth.) Benth. rattan ethanol extract allowed to isolate compounds characterized as β-sitosterol, triacontane, hexacontane, quercitin, myricitrin, 2,4,6-trimethoxyphenol-1-O-β-D-(6'-O-galloy1)-glucopyranoside, 5,7,3',4',5'-hexamethoxyflavone and oblongixanthone A. Oblongixanthone A was isolated for the first time and its structural characterization was obtained on the basis of extensive NMR and MS spectral studies.